2006
DOI: 10.1186/1472-6882-6-28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long term combined yoga practice on the basal metabolic rate of healthy adults

Abstract: BackgroundDifferent procedures practiced in yoga have stimulatory or inhibitory effects on the basal metabolic rate when studied acutely. In daily life however, these procedures are usually practiced in combination. The purpose of the present study was to investigate the net change in the basal metabolic rate (BMR) of individuals actively engaging in a combination of yoga practices (asana or yogic postures, meditation and pranayama or breathing exercises) for a minimum period of six months, at a residential yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 19 publications
3
43
0
1
Order By: Relevance
“…Even small savings in energy for those with more restricted mobility could be functionally important, allowing activity for a longer pe- (Newman, 2007). The effect of yoga on body function may be related to decreased arousal or a decrease in sympathetic nervous system activity (Chaya, 2006). To our knowledge, to date literature is witness of lack of project to study the effect of yoga intervention on walking speed and endurance in MS population.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Even small savings in energy for those with more restricted mobility could be functionally important, allowing activity for a longer pe- (Newman, 2007). The effect of yoga on body function may be related to decreased arousal or a decrease in sympathetic nervous system activity (Chaya, 2006). To our knowledge, to date literature is witness of lack of project to study the effect of yoga intervention on walking speed and endurance in MS population.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed yoga practice (relaxation techniques specially) can improve metabolic rate (Raju, 1994) and at the same time saving energy that may lead to decrease physical fatigue in daily activities. On the other hand, it has been reported that Hatha yoga produces improvements in mood (Berger, 1998) and calming of mind (Chaya, 2006) and may be effective to reduce mental fatigue. However, FFS do not distinguish physical and mental fatigues (Oken, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During slow breathing baroreflexs sensitivity also high compared to the normal breathing 13 . It stimulates the theta amplitude and delta waves, which is indicate the parasympathetic state arousal 14 . Pranayama activates the pulmonary stretch receptors and which induce the duration & frequency of inhibitory neural impulses 15. Lung inflation is a main physiological stimulus to release lung surfactant and prostaglandins into alveolar space and it reduces the tone of bronchial smooth muscle 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Так, медитация и йога, основанная на релаксации, снижают активность метаболиче-ских процессов в организме. Напротив, большин-ство асан, сопряженных с высокой мышечной активностью, и "интенсивные" виды пранаям (Уджайи-пранаяма, Сурья Анулома Вилома) приво-дят к интенсификации основного обмена [39]. При этом авторы отмечают, что кратковременное (4-8 нед.)…”
Section: механизмы влияния йоги на сердечно-сосудистую системуunclassified